Are Methylaluminoxane Activators Sheets?. Issue 13 (14th June 2021) - Collins, Scott; Hasan, Galib; Joshi, Anuj; McIndoe, J. Scott; Linnolahti, Mikko
Abstract: Density functional theory calculations on neutral sheet models for methylaluminoxane (MAO) indicate that these structures, containing 5‐coordinate and 4‐coordinate Al, are likely precursors to ion‐pairs seen during the hydrolysis of trimethylaluminum (Me3 Al) in the presence of donors such as octamethyltrisiloxane (OMTS). Ionization by both methide ([Me] − ) and [Me2 Al] + abstraction, involving this donor, were studied by polarizable continuum model calculations in fluorobenzene (PhF) and o‐difluorobenzene (DFB) media. These studies suggest that low MW, 5‐coordinate sheets ionize by [Me2 Al] + abstraction, while [Me] − abstraction from Me3 Al‐OMTS is the likely process for higher MW 4‐coordinate sheets. Further, comparison of anion stabilities per mole of aluminoxane repeat unit (MeAlO)n, suggest that anions such as [(MeAlO)7 (Me3 Al)4 Me] − =[7, 4 ] − are especially stable compared to higher homologues, even though their neutral precursors are unstable. Abstract : Hydrolysis of trimethylaluminum (Me3 Al) : Viewed through the lenses of electrospray ionization mass spectrometry and density functional theory, methylaluminoxane activators adopt sheet structures while the larger sheets form chelated anions on reaction with neutral donors. Calculated ion‐pair stabilities in polar media agree well with experimental spectra collected during formation of activators.